PAULO FREIRE’S HUMANISM PARADIGM IN THE TRANSFORMATION OF 21ST CENTURY EDUCATIONAL MANAGEMENT: A CRITICAL ANALYSIS OF CURRENT EDUCATIONAL MANAGEMENT PRACTICES - Ujang Syarip Hidayat; Giri Verianti; Wiwin Winarni; Asep Zuhara Argawinata (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
This study analyzes educational management practices in 21st-century Indonesia through the lens of Paulo Freire’s dialogical humanism, highlighting the gap between human-centered educational demands and school management practices dominated by bureaucratic-technocratic paradigms. The study employs a multiple-case study design across six secondary schools to examine how administrative compliance logic and hierarchical culture shape spaces for dialogue, critical reflection, and transformative action. Findings reveal that the dominance of bureaucratic management leads to various disparities, including teacher alienation, pseudo participation, digital divides, and the dehumanization of educational processes, while limiting meaningful dialogue and praxis. However, evidence suggests that integrating Freirean principles of dialogue, conscientização, praxis, and liberation can encourage the transformation of educational management toward greater participation, inclusion, and emancipation. The study concludes that such transformation requires administrative reform, strengthening reflective capacity, and leveraging local values and digital technology to realize educational management that is humanistic and relevant to the needs of the 21st-century.